THE Internalization Of Islamic Business Ethics In SMES: A Case Study Of Markisaku Syrup Industry - Elce Purwandari; Mohammad H. Holle; Luhgiatno; Diana Widhi Rachmawati; Andiwijaya; Erwan Iskandar (Universitas Islam Darul 'ulum Lamongan, 2026)
This study explores the internalization of Islamic business ethics in a Small and Medium Enterprise (SME) and its implications for trust and business sustainability. Using a qualitative case study approach, the research was conducted at the Markisaku Syrup enterprise through in-depth interviews, observations, and document analysis. The findings show that ethical values honesty, justice, transparency, and care are embedded in daily business practices through leadership example and routine activities rather than formal governance systems. Honesty and justice are strongly reflected in product quality, fair employee treatment, and equitable business relationships. Transparency is partially implemented, particularly in product information, while financial reporting remains less structured due to resource limitations. The study also reveals that ethical practices play a crucial role in building trust among consumers, employees, and business partners. This trust strengthens relationships and supports long-term business sustainability. The findings suggest that practice-based ethical internalization can serve as a strategic foundation for SME development, even in the absence of formal institutional structures.